Role of maintenance management of rolling stock in Bangladesh Railway : a study to assess effectiveness and efficiency - Islam, Md. Shafiqul (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.